Moderasi Beragama dalam Bingkai Globalisasi dan Multikulturalisme di Indonesia - Fajar Khaswara (UIN Sunan Gunung Djati Bandung, 2022)
Religious moderation is an important value that must be fought for in the current era of globalization. This attitude of religious moderation can certainly prevent the emergence of extremism in society. This study aims to discuss religious moderation through various views and relate it to current phenomena such as globalization, multiculturalism, and Indonesianess. The research methodology carried out in this research is to use qualitative research methods using literature studies. The results of this study contain the relationship between globalization, multiculturalism, Indonesianess, extremism, and religious moderation. The conclusion of this study shows that religious moderation mediates the emergence of religious extremism and liberalism. Religious moderation can be campaigned through social media in the current era of technological globalization.